Tracing the Trail of Wisdom: the Construction of Arabic-Language Comics Based Kh’s Inspiring Story Abdul Wahab Hasbullah - Hidayah, Maslahatul; Rahmawati, Rina Dian (Shaut al Arabiyyah, 2024)
The research aims to develop Arabic Comics products Based on the Inspirational Stories of KH Abdul Wahab Hasbullah. Equipped with conversations and illustrations. Students are expected to improve their Arabic language skills. Research objectives; Giving birth to Comic products as a learning medium for students of class X MAI Bahrul Ulum Tambakberas Jombang, Describing the feasibility of Comics as a learning medium for students of class X MAI Bahrul Ulum Tambakberas Jombang, Describing the improvement of Arabic language skills of students of class X MAI Bahrul Ulum Tambakberas Jombang between before and after. Types of research Research and Development. Borg & Gall development model. The subject of the trial is class X MA. Al-I'dadiyyah Bahrul Ulum Tambakberas Jombang. The results of the validation of media experts and linguists are valid. The average result of media experts is 95%, linguists 93%. The results of individual trials are 100% in agreement, the results of small-scale trials are 94% in agreement, and the results of field trials are 83% in agreement. The average pre-test result was 74, post-test 83. Showing the increasing mastery of Arabic vocabulary in interacting through comic media.